Hubungan Brand Image, Brand Prestige, Lifestyle, dan Social Influence dengan Keputusan Pembelian Produk Tiruan Merek Chanel - Aulia Ratri Kusumastuti; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Nowadays, fashion product is not only become a necessity but also a Lifestyle. Along with the development of the fashion industry, it is undeniable that counterfeit products are also present to meet the needs of people on fashion products. The higher consumer interest in luxury brands often clashes with economic ability, so to fulfill the needs of this low-end consumer market, counterfeiting takes place. One of the many luxury branded products in circulation are counterfeit products of Chanel brand. The growth of the production level of imitation goods is offset by the amount of consumption, so indirectly the consumers are involved in the development of imitation products in Indonesia. The purpose of this study is to determine the relationship between Brand Image, Brand Prestige, Lifestyle, and Social Influence with purchase decision on counterfeit products of Chanel brand. This research used the research’s result of Brand Image impact for purchase decision, Conspicuous Consumption Model, Consumer Decision Model, and Social Communication Theory. This research is explanatory quantitative research. The sampling technique used is non probability sampling techinque with purposive sampling approach. The sample of this research are women in age 15 until 40 years old who know Counterfeit Products of Chanel Brand in Semarang City. The sum of respondents are 50 from all the population which had been taken by purposive sampling technique. Based on the hypothesis test conducted using Chi-Square with SPSS program, the test result between each variable X with variable Y is the significance value is less than 0,01 which means very significant. The test results show that Brand Image has a positive relationship with purchase decision on counterfeit products of Chanel brand and Brand Prestige also has a positive relationship with purchase decision on counterfeit products of Chanel brand. Meanwhile, the test results about relationship between Lifestyle and Social Influence with purchase decision on counterfeit products of Chanel brand can not be concluded. Suggested with these results, the test using Chi-Square should use more samples. In addition, business people can improve the image and prestige on their brand so that consumers are confident in making a purchase.